2016
DOI: 10.1371/journal.pone.0146770
|View full text |Cite
|
Sign up to set email alerts
|

MiR-1303 Regulates Mycobacteria Induced Autophagy by Targeting Atg2B

Abstract: MicroRNAs are emerging post-transcriptional regulators of gene expressions in both innate immunity and adaptive immunity. In mycobacteria infection, autophagy plays an important role in innate defense mechanism and is tightly regulated by the autophagy-related proteins. Here, we show that Atg2B is involved in the regulation of mycobacteria-induced autophagy. MiR-1303, which function is not defined yet, is found to negatively regulate mycobacteria-induced Atg2B protein production, ultimately down-regulate mycob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Autophagy is tightly controlled by a family of autophagy regulators, autophagy-related proteins (Atgs), and their homologs and regulated by different signaling pathways such as mitogen-activated protein kinase (MAPK), phosphatidylinositol 3-kinase (PI3K), and mammalian target of rapamycin (mTOR), 17 , 18 which coordinate autophagy through regulating autophagosome formation and autophagosome-lysosome fusion. In this study, we screened and identified miRNAs from Salvia miltiorrhiza and investigated whether and, if so, how the identified miRNA regulates autophagy in angiotensin II (Ang II)-stimulated VSMCs and mouse AAA models.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is tightly controlled by a family of autophagy regulators, autophagy-related proteins (Atgs), and their homologs and regulated by different signaling pathways such as mitogen-activated protein kinase (MAPK), phosphatidylinositol 3-kinase (PI3K), and mammalian target of rapamycin (mTOR), 17 , 18 which coordinate autophagy through regulating autophagosome formation and autophagosome-lysosome fusion. In this study, we screened and identified miRNAs from Salvia miltiorrhiza and investigated whether and, if so, how the identified miRNA regulates autophagy in angiotensin II (Ang II)-stimulated VSMCs and mouse AAA models.…”
Section: Introductionmentioning
confidence: 99%
“…Gene ontology (GO) analysis revealed that some of the identified target genes participate in the development of the immune and nervous systems (Table 4). For instance, miR-190b [19] and miR-1303 [20] regulate the expression of neuronal growth regulator 1 (NEGR1) [21], which belongs to an adhesion proteins family and has an important role in neurite outgrowth during the process of neuron development. It is also possible that regulation of this process is probably related to neuropathic pain resulting from HZ, however the specific mechanism remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…And our studies have confirmed that ATG2B is a direct target of miR‐130a by luciferase assays. Meanwhile, miR‐143 targets ATG2B to inhibit autophagy and increase inflammatory reactions in Crohn's disease, and miR‐1303 also regulates mycobacteria‐induced autophagy by targeting ATG2B, 38,39 which indicated that ATG2B is the direct target of miR‐130a to regulate autophagy in VSMCs.…”
Section: Discussionmentioning
confidence: 99%